2024
DOI: 10.1088/1402-4896/ad1957
|View full text |Cite
|
Sign up to set email alerts
|

4D printing of porous PLA-TPU structures: effect of applied deformation, loading mode and infill pattern on the shape memory performance

Davood Rahmatabadi,
Kianoosh Soltanmohammadi,
Mohammad Aberoumand
et al.

Abstract: For the first time, the synergy of shape memory polymer (SMP) blending, 4D printing, and cold programming (CP) are investigated for improving the functionality of the shape memory effect (SME), increasing medical applications of porous structures, direct programming, and removing current limitations. Porous PLA-TPU structures with different printing patterns and applied deformation were CPed under constrained and non-constrained compression modes at room temperature and were recovered in the rubbery phase. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Therefore, the amount of programming stress for the vertical pattern is 1.23 times more than the horizontal. In the case that the grids and rasters are in the direction of applying force, they show more resistance than when the force is applied in the direction perpendicular to them [31]. This difference is more profound in the stretching mode.…”
Section: Constrained Shape Memory Cyclementioning
confidence: 98%
“…Therefore, the amount of programming stress for the vertical pattern is 1.23 times more than the horizontal. In the case that the grids and rasters are in the direction of applying force, they show more resistance than when the force is applied in the direction perpendicular to them [31]. This difference is more profound in the stretching mode.…”
Section: Constrained Shape Memory Cyclementioning
confidence: 98%
“…Davood Rahmatabadi et al demonstrated that by incorporating just 30% TPU (thermoplastic polyurethane) with 70% PLA (polylactic acid) in a composite manufactured through fused deposition modeling 3D printing, they significantly improved the shape memory performance [49]. Their composite displayed shape fixity and shape recovery rates of up to 100% and 91%, respectively.…”
Section: Application To the Manufacture Of Heart Valve Structuresmentioning
confidence: 99%
“…Furthermore, the 4D printing technique has emerged as a powerful tool for creating objects tailored for biomedical implants and smart textiles. By leveraging materials like PVC [2,3] and porous PLA-TPU [4], 4D printing enables the fabrication of structures capable of dynamically changing shape in response to external triggers. However, the challenge of poor mechanical properties in SMPs can be effectively addressed by harnessing the unique characteristics of nanofillers [5].…”
Section: Introductionmentioning
confidence: 99%